Dual inhibition of FAS and HAS2/3 by 4-MU in Realgar-Coptis chinensis unveils a metabolic checkpoint for liver cancer therapy - Songtao Wu; Yingying Wang; Denghui Deng; Guohua Zheng; Hanxiang Mei; Cong Wang; Xiang Zheng; Chun Gui; Fei Liao; Meixian Xiang (Natural Products and Bioprospecting)
Abstract Modern pharmacology has found that both Realgar and Coptis chinensis can induce apoptosis in tumor cells, and traditional Chinese medicine theory suggests the possibility of combining the two, however, the specific mechanisms involved have not been elucidated. This study investigated the therapeutic mechanism of the Realgar-Coptis chinensis drug pair (RCCD) against hepatocellular carcinoma (HCC) by identifying its key active compounds and targets. Through integrated LC–MS analysis, transcriptomics, network pharmacology, and bioinformatics, we identified the mechanism of action, key bioactive compounds, and core targets. Molecular docking, molecular dynamics simulations, and microscale thermophoresis (MST) validated the binding affinity between key compounds and core targets. TIMER2.0 database was used to analyze the relationship between the core targets and HCC. H22 tumor xenograft mouse model and immunohistochemistry and pathology analyses were performed to validate the antitumor efficacy of the active compounds. RCCD has a high degree of selectivity of lipid metabolism pathway, 4-Methylumbelliferone (4-MU) was the key active compound with strong binding activity to the core target fatty acid synthase (FAS), and 4-MU down-regulated the expression of FASN in tumor tissues and induced apoptosis in HCC cells. In addition, as a hyaluronan synthase (HAS2/3) inhibitor, 4-MU interfered with the HA-dependent tumor microenvironment and fibrosis process by inhibiting HAS2/3. Thus, 4-MU may inhibit tumor progression by inhibiting FAS and HAS2/3. 4-MU extracted from RCCD exerts anti-HCC effects by modulating the activities of FAS and HAS2/3, thereby reprogramming lipid metabolism and regulating hyaluronan synthesis. Graphical Abstract